Guinea : Basic Agricultural Public Expenditure Diagnostic Review (2003-2012), Main Report - World Bank (Washington, DC, 2014)
The Guinean government assigns a crucial role to agriculture in accelerating growth, reducing poverty, and creating jobs. This role is inscribed in Poverty Reduction Strategy Paper (PRSP) 3, which was approved by the government in May 2013, following PRSP 2 (2007-2010) and PRSP 1 (2002-2006). As part of the revival of its agricultural development strategy, the government through the Ministry of Agriculture expressed its desire for an agricultural public expenditure review to be carried out in order to learn from past experience and to improve performance in the medium term. This request was accepted by the NEPAD Planning and Coordinating Agency. The cost of this review was met by the strengthening national comprehensive agricultural public expenditure in Sub-Saharan Africa program and co-funded by the Bill and Melinda Gates Foundation and the CAADP Multi-Donor Trust Fund. The goals of the 2003-2012 agricultural public expenditure review in Guinea are as follows: gain a better understanding of the country's performance in the context of the 2003 Maputo declaration; seek and recommend corrective actions for existing programs and suggest appropriate actions for future programs with a view to improving their impact and making them more efficient and equitable; and increase the visibility of the government and the DPs over the sector's absorptive capacity so that the decision may be made to allocate more resources to agricultural development.